2015
DOI: 10.1159/000369692
|View full text |Cite
|
Sign up to set email alerts
|

MiR-133b Promotes Neurite Outgrowth by Targeting RhoA Expression

Abstract: Background: MicroRNA-133b (miR-133b) has been shown to play a critical role in spinal cord regeneration. The aim of this study was to investigate the cellular role of miR-133b in neural cells. Methods: PC12 cells and primary cortical neurons (PCNs) were transfected with lenti-miR-133b, lenti-miR-133b inhibitor, plasmid-shRNA-RhoA, plasmid-RhoA and their negative controls. After 48 hours of transfection, the levels of proteins and mRNA or miRNA were evaluated by Western blotting and qRT-PCR, respectively. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 48 publications
(58 reference statements)
4
56
0
Order By: Relevance
“…RhoA plays important pathophysiological roles in the cardiovascular system and in disease states such as hypertension, heart failure, stroke, diabetes and others [22,23]. We found that RhoA activation and geranylgeranylation of RhoA in the tissue of the heart increased at week 6 of SHR although there was no significant difference, but it significantly increased at week 12 of SHR (data not shown).…”
Section: Discussionmentioning
confidence: 76%
“…RhoA plays important pathophysiological roles in the cardiovascular system and in disease states such as hypertension, heart failure, stroke, diabetes and others [22,23]. We found that RhoA activation and geranylgeranylation of RhoA in the tissue of the heart increased at week 6 of SHR although there was no significant difference, but it significantly increased at week 12 of SHR (data not shown).…”
Section: Discussionmentioning
confidence: 76%
“…The ROCK2 transcript is highly expressed in muscle and brain tissues, whereas the ROCK1 is localized in nonnerves tissues [37]. RhoA/ROCK pathway has been shown to play an important role in neurite growth inhibition from CSPG after CNS injury [38]. Several preclinical and clinical studies have utilized inhibitors of Rho/ROCK signaling pathway for anticancer therapeutics in prostate, lung, melanoma, and many other tumor types with remarkable success [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-133b, which is specifically expressed in mammalian midbrain dopaminergic neurons (DNs) and is deficient in midbrain tissue from patients with Parkinson's disease [89], has been proved as an important determinant in spinal cord regeneration in adult zebra fish by directly reducing RhoA protein levels [90]. miR-133b has also been shown to be promoting neurite outgrowth in the primary cortical neurons and PC12 cells [91]. miR-133b increases axon growth and attenuates axon growth restrictions from CSPG in PCNs via ERK1/2 and PI3K/Akt signaling pathway by suppressing RhoA [91].…”
Section: Micrornas and Intrinsic Determinants Of Axon Regenerationmentioning
confidence: 99%
“…miR-133b has also been shown to be promoting neurite outgrowth in the primary cortical neurons and PC12 cells [91]. miR-133b increases axon growth and attenuates axon growth restrictions from CSPG in PCNs via ERK1/2 and PI3K/Akt signaling pathway by suppressing RhoA [91]. …”
Section: Micrornas and Intrinsic Determinants Of Axon Regenerationmentioning
confidence: 99%